About the deployments of the neighborhood unit. the communitarian space in leon krier´s polycentric city (2006)
The present article emphasizes a conceptual analysis of collective places proposed by the Polycentric City of Leon Krier. The initial distinction between concepts of “communitarian place” and “public place” help us to show an attempt to approach – undertaken in the speech – the project of the Polycentric City to the concept of “public place”, such as it was defined by Italian Type-Morphology. However, the exposition of the existing similarities between the Neighborhood Unit, of Clarence A. Perry, and the Polycentric City reveals the concept of communitarian place as a concept-key to understand the urban project of Leon Krier.